The Complementary Relationship Between Echocardiography and Multi-Slice Spiral CT Coronary Angiography in the Diagnosis of Coronary Artery Thrombosis in Children With Kawasaki Disease - Xu, Yun-ming; Chu, Yan-qiu; Li, Xue-mei; Wang, Ce; Ma, Quan-mei; Yu, Xiao-na; Yu, Xian-yi; Chen, Rui; Xing, Yan-lin; Yu, Xue-xin; Sun, Le; Cui, Xiao-zhe; et al. (Frontiers in Pediatrics, 2021)
Aim: To compare the diagnostic values by using transthoracic echocardiography (ECHO) and multi-slice spiral CT coronary angiography (CTCA) for identifying coronary artery thrombosis in children with Kawasaki disease (KD). Methods: Total 97 KD children with coronary artery dilation complications in our hospital from June 2012 to December 2020 were included in the study. CTCA and ECHO were performed after over 1 month of illness. Results: Coronary artery thrombosis was found in 14 out of 97 patients. Among them, 10 were identified as positive by CTCA, 9 were identified as positive by ECHO, and 5 were identified as positive by both CTCA and ECHO. Conclusion: Both CTCA and ECHO can be used to diagnose coronary artery thrombosis. ECHO has advantage in identifying low-density thrombus, and CTCA is better for the clot in distal coronary artery. They can complement each other.